EFEKTIVITAS PENYULUHAN KESEHATAN GIGI DENGAN MENGGUNAKAN MEDIA BUSY BOOK TERHADAP TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT - Nailul Husna; Prasko Prasko (Jurnal Kesehatan Gigi, 2019)
Children are vulnerable to caries and other dental diseases because they still need help from parents and families to guide them in maintaining the cleanliness of their teeth and mouth. One effort to improve dental and oral health is by maintaining dental and oral health. However, people often ignore their dental and oral health problems caused by lack of knowledge of dental and oral health. Insufficient knowledge about dental and oral hygiene is one reason that children ignore dental and oral health problems. One of the ways to improve dental and oral health knowledge is through dental and oral health education. And success in efforts to educate dental health in school children is inseparable from the educational method and the importance of the role of a media because it can support the learning process, facilitate students in understanding learning material. Through the media, the messages delivered can be more interesting and easy to understand. One of the media used is busy book. The purpose of this study was to determine the effectiveness of the busy book media on the level of dental and oral health knowledge in grade 3 elementary school students. The type of this study was quantitative with a quasi-experimental method with a pretest-posttest group design study design. The sample of this study was grade 3 students of SDN Rowocacing in Pekalongan Regency with 18 students from the busy book group. Data analysis using Wilcoxon test and Mann-Whitney test. The results of the statistical test with the Wilcoxon test showed that there were differences in knowledge between before and after counseling, the value of p-value of busy media book = 0,000 means that there were differences before and after counseling using the busy book media. The Mann-Whitney test showed that there was a significant difference in effectiveness between counseling and the busy book media on increasing dental and oral health knowledge with p-value = 0.02.